SOCIAL RELIGIOUS CHANGES OF EAST JAVA PEOPLE IN THE INDEX OF TOLERANCE ANALYSIS - Muhammad Lukman Hakim; Indah Dwi Qurbani; Abdul Wahid (Jurnal Sosiologi Agama, 2021)
The author looks at the inverse social reality looking at Indonesia’s rankings. In fact, in 2009, Indonesia was classified as a country with full freedom. Saiful Mujani (2019) believes that the decline in freedom in Indonesia is strongly related to religious or minority intolerance. Researchers see in East Java there are still cases related to acts of tolerance. The study applies Van Der Walt’s model for religious tolerance (2014) which has seven key indicators, those (a) minimizing religious differences, (b) inclusivity, (c) exclusivity and selfishness, (d) openness to change, (e) faith and respect for others, (f) religious beliefs, and (g) recognizing the freedom of others. The data for this study was collected by conducting surveys in 38 regions in East Java. The number of survey respondents was 402 and the study found that the level of religious tolerance in East Java in 2020 was 73.9 (out of 100). This is proof that religious tolerance in East Java is categorized as “good”. The highest score is on the first indicator which is 82 and the lowest score is on the sixth indicator which is 63.4. This finding is expected to be a government policy recommendation for its development program in East Java.